PRESTIGE AND NATIONAL IDENTITY AS PREDICTORS OF FOOD PRODUCTS PURCHASE - Šapić, Srđan; Furtula, Srđan; Durkalić, Danijela (Economics of Agriculture, 2018)
In modern living conditions, consumers have access to a greater offer of food products than ever before. In addition to local food products, the growth of foreign food products is noticeable, which signifcantly intensifes competition in this sector. The paper analyzes whether and how national identity and prestige affect the assessment of local food products and whether this assessment affects readiness to buy them. The research objective is to show whether national identity influences the purchase of local food products among consumers in Serbia, and whether prestige is important for the purchase process, as is the case with other product categories. The main research results indicate that the prestige factor has an impact on the assessment of both local and foreign food products, while the national identity factor has an impact only on local food product assessment. Also, research results indicate that food product assessment has an impact on the purchase of both local and foreign food products.